How consumer-generated images shape important consumption outcomes in the food domain. Issue 1 (11th January 2016) - Coary, Sean; Poor, Morgan
Abstract : Purpose: – The purpose of the present research is to investigate consumer-generated images (CGI), or images of products and experiences that are produced and controlled by consumers, particularly in the food domain, and the influence that producing such images has on the consumer creating the image. Design/methodology/approach: – The authors present three studies that manipulate the type of food (indulgent vs healthy) and whether participants create CGI prior to consumption. Data were analyzed using a combination of ANOVA and PROCESS. Findings: – It is shown that producing CGI causes a momentary active delay in consumption, which increases the savoring associated with consumption of pleasurable (i.e. indulgent) foods and, in effect, increases attitudes and taste evaluations of the experience when consumption actually takes place. When descriptive social norms regarding healthy eating are made salient, CGI can also lead to more favorable outcomes for less pleasurable (i.e. healthy) foods. Practical implications: – The findings provide insight into the effects of consumers taking pictures of their food before consumption, a growing trend on social media sites (i.e. Instagram). Marketing managers can develop strategies to encourage their consumers to take pictures of their food. Originality/value: – To the best of the authors' knowledge, this research is the first to demonstrate the effects of consumer-generated images on a product consumption experience and identify the conditions and process under which these effects occur.